Cancer Therapy Targeting the HER2-PI3K Pathway: Potential Impact on the Heart - Klement, Giannoula L.; Goukassian, David; Hlatky, Lynn; Carrozza, Joseph; Morgan, James P.; Yan, Xinhua (Frontiers in Pharmacology, 2012)
The HER2-PI3K pathway is the one of the most mutated pathways in cancer. Several drugs targeting the major kinases of this pathway have been approved by the Food and Drug Administration and many are being tested in clinical trials for the treatment of various cancers. However, the HER2-PI3K pathway is also pivotal for maintaining the physiological function of the heart, especially in the presence of cardiac stress. Clinical studies have shown that in patients treated with doxorubicin concurrently with Trastuzumab, a monoclonal antibody that blocks the HER2 receptor, the New York Heart Association class III/IV heart failure was significantly increased compared to those who were treated with doxorubicin alone (16 vs. 3%). Studies in transgenic mice have also shown that other key kinases of this pathway, such as PI3Kα, PDK1, Akt and mTOR, are important for protecting the heart from ischemia-reperfusion and aortic stenosis induced cardiac dysfunction. Studies, however, have also shown that inhibition of PI3Kγ improve cardiac function of a failing heart. In addition, results from transgenic mouse models are not always consistent with the outcome of the pharmacological inhibition of this pathway. Here, we will review these findings and discuss how we can address the cardiac side-effects caused by inhibition of this important pathway in both cancer and cardiac biology.